(untitled) (Annual of the Faculty of Philosophy in Skopje, 2024)
Тhe text outlines Tertullian’s stances on the catastrophic unification (by way of marriage) of the daughters of men with the sons of God from the story about the fallen angels. The offspring produced by this merger is horrifically dangerous to the human race on earth, and therefore, Tertullian’s aim is to prevent any sort of reactualization of such a disastrous event. He communicates this through his positions on the primordial sinfulness of the woman, and the blame cast onto the beautiful daughters of men, who, with their unhumble and uncovered beauty tempted the angels so strongly, that they caused them to abandon their celestial abodes and functions, and descend to earth, thus disrupting the order in the world, and bringing people problematic knowledge and various problematic capabilities, of which the еvilest were those most appealing to the women. Tertullian’s aim is to insist on the necessity of the covering of women, especially virgins, since those were the errant daughters of men from the story, so that they do not pose a danger to the chastity of men, and more importantly, to the innocence, morality and the ontological stability of the angels, and with this, the structure and functioning of the religious community. These objectives are overviewed through his polemic with Marcion, and through his strong opposition to the customs of uncovering by a part of the women within the church(es). Through chosen examples from Tertullian’s opus, the instances in which he mentions the motif of the fallen angels through the blame and sin of the daughters of men, and the need to prevent any such transgression are shown.